MARKETING EFFICIENCY ANALYSIS OF PALM OIL SYRUP BROWN SUGAR IN LAU TADOR VILLAGE - Hafifuddin Hasfa Marpaung; Tuty Ningsih; Tifany Zia Aznur (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aimed to identify the marketing channel patterns and analyze the marketing efficiency of palm sap brown sugar in Laut Tador Village, Batu Bara Regency, North Sumatra Province. The research was conducted from February to April 2026 using a mixed-methods approach that combined quantitative and qualitative methods. Respondents were selected using the snowball sampling technique, involving producers and marketing institutions. Data were collected through observations, interviews, documentation, and literature reviews. The data were analyzed descriptively by calculating marketing costs, marketing margins, farmer's share, benefit-cost ratios, and marketing efficiency. The results revealed two marketing channel patterns: Channel I (producer–consumer) and Channel II (producer–retailer–consumer). Channel I incurred a marketing cost of IDR 195/kg, generated a marketing margin of IDR 7,689/kg, a profit of IDR 7,494/kg, a farmer's share of 100%, a profit-to-cost ratio of 38%, and a marketing efficiency value of 1.08%. Meanwhile, Channel II recorded a total marketing cost of IDR 371/kg, with marketing margins of IDR 5,181/kg at the producer level and IDR 2,362/kg at the retailer level. The total profit amounted to IDR 7,173/kg, consisting of IDR 5,136/kg for producers and IDR 2,037/kg for retailers. The farmer's share in Channel II was 87.12%, while the profit-to-cost ratios were 110.9% for producers and 6.24% for retailers. The marketing efficiency values were 0.28% at the producer level and 1.77% at the retailer level. Based on all evaluated indicators, both marketing channels were classified as efficient. However, Channel I was found to be more efficient because it had a shorter marketing chain, lower marketing costs, and provided a larger share of the final price and higher profits to producers.